Development of Contextual-Based E-LKPD to Improve the Ability to Understand Fraction Concepts - Sakinah, Sakinah; Dewi, Ratna Sari; Hakim, Zerri Rahman (Universitas Pendidikan Indonesia Kampus Serang, 2023)
The ability to understand concepts is basic in learning mathematics, which is essential for students to have so that students can understand the concepts of the material being studied. This study thus aims to determine feasibility, improve the ability to understand the concept of fractions, and find out students' responses to contextually-based E-LKPD (e-student worksheets). This research was conducted at SDN Sepang with 32 students in class V elementary school as subjects. This study used the Research and Development (RD) method, with ADDIE (analysis, design, development, implementation, evaluation) stages. Data collection was obtained using questionnaires, interviews, documentation, and tests. The study results showed that (1) the feasibility of contextually based E-LKPD was in a very decent qualification with an average percentage of the feasibility of 86% for material experts, 90% for media experts, and 90% for linguists. (2) There was an increase in students' understanding of fractions after using the E-LKPD with an N-gain of 0.61, with moderate qualifications. (3) The average percentage of student responses was 83% in the small group test and 89% in the group test, with very good qualifications. Based on the trial results, it can be concluded that contextually based E-LKPD was very feasible to use and could improve the ability to understand fraction concepts and obtain excellent student responses. Electronic worksheets combined with contextual content could be an alternative to be developed in other conceptual learning.